2015
DOI: 10.1155/2015/520619
|View full text |Cite
|
Sign up to set email alerts
|

An Exploratory Analysis of the Relationship between Cardiometabolic Risk Factors and Cognitive/Academic Performance among Adolescents

Abstract: This exploratory study examines the relationship between cardiometabolic risk factors (blood pressure, waist circumference, BMI, and total cholesterol) and cognitive/academic performance. In this study, 1297 Taiwanese tenth-grade volunteers are recruited. Scores from the Basic Competency Test, an annual national competitive entrance examination, are used to evaluate academic performance. Cognitive abilities are accessed via the Multiple Aptitude Test Battery. The results indicate that systolic blood pressure i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
1
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 42 publications
1
9
1
3
Order By: Relevance
“…The present study does not find any associations between sysBP and executive functions, which corroborates several studies in youth [ 20 , 23 ]. However, others found that children and adolescents with sysBP ≥ 90th percentile performed poorer on a working memory task compared to their normotensive peers [ 22 , 42 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The present study does not find any associations between sysBP and executive functions, which corroborates several studies in youth [ 20 , 23 ]. However, others found that children and adolescents with sysBP ≥ 90th percentile performed poorer on a working memory task compared to their normotensive peers [ 22 , 42 ].…”
Section: Discussionsupporting
confidence: 93%
“…Results from our study did not show any associations between the MetS-cluster score and measures of executive function. To date, only a few studies have investigated the associations between clustered metabolic risk and executive functions in children or adolescents [ 20 23 ]. Yau et al (2012) found that adolescents with MetS performed worse on measures of mental flexibility compared to adolescents without symptoms of MetS.…”
Section: Discussionmentioning
confidence: 99%
“…La hipertensión arterial, el índice de masa corporal superior al rango normal, la elevación del nivel de colesterol, la circunferencia de la cintura superior al normal, la diabetes mellitus, entre otros, se constituyen como los principales factores de riesgo de enfermedad cardiovascular y síndrome metabólico 33 . Además como factores de riesgo agregado para el desarrollo del síndrome metabólico, se suman el tabaquismo, alcoholismo, uso y abuso de drogas, dieta inadecuada y falta de ejercicio 34 .…”
Section: Discapacidad Cognitiva Y Riesgos Cardiometabólicosunclassified
“…Personas con hipertensión dan cuenta de rendimientos deficientes en tareas de atención, aprendizaje y memoria, funciones ejecutivas, habilidades visoespaciales, habilidades psicomotoras y de percepción. Por otro lado, personas con hipotensión tuvieron un rendimiento deficiente en tareas de memoria verbal a corto plazo, cálculo mental, función ejecutiva, atención selectiva y reconocimiento verbal, ambos grupos comparados con población normotensa 33 . Los pacientes con diabetes mellitus poseen un perfil neuropsicológico de deterioro cognitivo con un patrón de disfunción fronto-subcortical.…”
Section: Discapacidad Cognitiva Y Riesgos Cardiometabólicosunclassified
See 1 more Smart Citation